Efektivitas Program Literasi terhadap Pemahaman Brain Rot pada Remaja Manggisan Asri Wonosobo - Faizi, Ahmad; Saputri, Wahyu Novi; Dwiyanningrum, Puput Aura Mukti; Amannuri, Amannuri; Rahmadani, Novia Ayu; Syafitri, Dzikra Nur; Maulana, Muhammad Ilham (Universitas Negeri Gorontalo, 2025)
The phenomenon of brain rot, associated with repetitive and fast-paced digital content, poses risks to adolescents’ literacy and critical thinking skills, thereby requiring educational interventions to raise awareness and promote healthier digital habits. This study aimed to evaluate the effectiveness of a literacy socialization program based on Participatory Action Research (PAR) combined with Focus Group Discussion (FGD) in improving adolescents’ knowledge of brain rot. The program was conducted on July 27, 2025, in collaboration with PIK-R Andongsili, involving 15 female adolescents aged 14–22 years. The intervention consisted of structured material presentation followed by group discussion using case studies and mind mapping activities. Knowledge was assessed using a pre-test and post-test design, and data were analyzed using the paired t-test after the Shapiro–Wilk normality test. The results showed a significant improvement in knowledge, with the mean score increasing from 6.60 before the intervention to 7.80 after, yielding a mean difference of 1.20 points (p = 0.004). Furthermore, the proportion of participants categorized as having good knowledge increased from 26.7% to 73.3%. These findings indicate that literacy socialization through PAR and FGD effectively enhanced adolescents’ understanding of brain rot.